2010
DOI: 10.2134/agronj2009.0145
|View full text |Cite
|
Sign up to set email alerts
|

Chickpea‐Wheat Rotation for Higher Production in a Humid Tropical Region

Abstract: A gronomy J our n al • Volu me 102 , I s sue 2 • 2 010 363 ABSTRACT Stagnation in grain production in the developing world has contributed to the current worldwide food crisis. Th e principle objective of this study was to evaluate the possibility of improving grain production in the tropical humid region by chickpea (Cicer arietinum L.) in rotation with wheat (Triticum aestivum L). A 3-yr fi eld experiment in Kenya included four short-rainseason (SRS) management practices (chickpea green manure [GM], mature c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Research has shown that large fractions of the N requirements for subsequent crops could be met with legumes (Hargrove, 1986; Mitchell and Teel, 1977; Touchton et al, 1984). Reports of wheat–temperate legume rotations have shown greater wheat yields than wheat grown with fertilizer (Danga et al, 2010). However, these improvements were highly variable (0 to >100%), which indicated organic N sources in continuous wheat‐based systems may be unreliable (Evans et al, 1991; MacKown et al, 2007; Nielsen and Vigil, 2005; Pikul et al, 1997; Vigil and Nielsen, 1998).…”
mentioning
confidence: 99%
“…Research has shown that large fractions of the N requirements for subsequent crops could be met with legumes (Hargrove, 1986; Mitchell and Teel, 1977; Touchton et al, 1984). Reports of wheat–temperate legume rotations have shown greater wheat yields than wheat grown with fertilizer (Danga et al, 2010). However, these improvements were highly variable (0 to >100%), which indicated organic N sources in continuous wheat‐based systems may be unreliable (Evans et al, 1991; MacKown et al, 2007; Nielsen and Vigil, 2005; Pikul et al, 1997; Vigil and Nielsen, 1998).…”
mentioning
confidence: 99%
“…Likewise, lower ratios of C/N, C/P and lignin contents in chickpea straw than wheat straw might also be the reason for quick chickpea straw residues degradation, which rapidly increased soil microbial biomass. Plant material with a low C/N ratio will decompose faster than materials with a high C/N ratio [44]. Organic carbon is used by the soil microorganism as an energy source and C for microbial organic material production which ultimately increases microbial biomass [45]; however, amendment in the soils with the different compositions follow different mineralization patterns and hence variable soil microbial biomass is produced.…”
Section: Microbial Biomass Carbonmentioning
confidence: 99%
“…In particular symbiotic N-fixation demands high phosphorous which consumes large amounts of energy [8] generating metabolism strongly depends upon availability of P [9]. Africa contributes to 0.4 -1% of world's green gram production.…”
Section: Introductionmentioning
confidence: 99%